Philosophical Views of Romanas Bytautas - Bagdonavičius, Vacys (Problemos, 1988)
The article deals with the philosophical views of the Lithuanian thinker R. Bytautas (1886-1915). First, the origins of the views are traced back, and then the character of the resulting philosophy is analysed. The philosophy is viewed as a compromise between idealism and materialism. However, the dominance of the idealistic tendencies is pointed out.